Trend of preventable deaths up to the 6th day of life in the state of São Paulo - 2008 to 2017 - Arnaldo Sala; Carla Gianna Luppi (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE: To analyze the trend of early neonatal infant mortality in the state of São Paulo according to preventability and region of residence. METHODS: Ecological study with secondary data from 2008 to 2017, obtained from the Sistema de Informação sobre Nascidos Vivos (Sinasc - Live Birth Information System) and the Sistema de Informação sobre Mortalidade (SIM - Mortality Information System). The causes of death were classified according to preventability groups, and the annual percentage changes in the death rates of each preventability group were estimated using the Joinpoint software. RESULTS: The early neonatal component showed a reduction trend with an annual percentage change of −1.18 (95%CI −1.63 to −0.72), less pronounced than the other age components of infant mortality. In the analysis according to preventability, the causes reducible by attention to the woman during pregnancy and those reducible by attention to the fetus and the newborn presented annual percentage change of −1.03 (95%CI: −1.92 to −0.13) and −2.6 (95%CI: −4.07 to −1.11), respectively. In the causes reducible by attention to women during delivery, no reduction trend was observed. Regional discrepancies occurred in the variation of early neonatal infant mortality rates according to type of preventability. CONCLUSIONS: Mortality up to the 6th day of life presented greater difficulty of reduction when compared with the other age components. The absence of a reduction trend in preventable deaths due to the attention to women during delivery points to possible fragility in the attention to delivery.